Cognitive rehabilitation following traumatic brain injury - Freire,Fabio Rios (2011)
Abstract Annually, some 500,000 people are hospitalized with brain lesions acquired after traumatic brain injury (TBI) in Brazil. Between 75,000 and 100,000 individuals die within hours of the event and 70,000 to 90,000 evolve to irreversible loss of some neurological function. The principal causes of TBI include motor vehicle accidents (50%), falls (21%), assaults and robberies (12%) and accidents during leisure activities (10%). Within this context, cognitive rehabilitation, a clinical area encompassing interdisciplinary action aimed at recovery as well as compensation of cognitive functions altered as a result of cerebral injury, is extremely important for these individuals. Therefore, the aim of this study was to review the basic concepts related to TBI, including mechanisms of injury, severity levels of TBI, the most common findings in moderate and severe TBI survivors, and the most frequent cognitive impairments following TBI, and also to discuss the strategies used to handle patients post-TBI. The study results yielded relevant information on a structured cognitive rehabilitation service, representing an alternative for patients and families afflicted by TBI, enabling the generation of multiple research protocols.